2020
DOI: 10.1016/j.sjbs.2020.09.041
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel bioactive molecules from garlic bulbs: A special effort to determine the anticancer potential against lung cancer with targeted drugs

Abstract: Garlic ( Allium sativum L.), is a predominant spice, which is used as an herbal medicine and flavoring agent, since ancient times. It has a rich source of various secondary metabolites such as flavonoids, terpenoids and alkaloids, which have various pharmacological properties. Garlic is used in the treatment of various ailments such as cancer, diabetes and cardiovascular diseases. The present study aims to explore the plausible mechanisms of the selected phytocompounds as potential inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 69 publications
0
6
2
Order By: Relevance
“…Hesperidin, nabiximols, pectolinarin, epigallocatechin gallate, and rhoifolin displayed lower binding free energies towards 7DDN protein of SARS-CoV-2, according to findings of this study. These compounds have the ability to act as antiviral phytochemicals, preventing the virus from replicating (Padmini et al, 2020;Li et al, 2020;Khare et al, 2020). These results constitute merely a preliminary examination to aid later tests, which will begin in animal models or human clinical trials.…”
Section: Phytochemicalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hesperidin, nabiximols, pectolinarin, epigallocatechin gallate, and rhoifolin displayed lower binding free energies towards 7DDN protein of SARS-CoV-2, according to findings of this study. These compounds have the ability to act as antiviral phytochemicals, preventing the virus from replicating (Padmini et al, 2020;Li et al, 2020;Khare et al, 2020). These results constitute merely a preliminary examination to aid later tests, which will begin in animal models or human clinical trials.…”
Section: Phytochemicalsmentioning
confidence: 99%
“…Intermolecular interaction involves hydrophobic, dispersion, or Van der Waals forces, H bonding, and electrostatic forces (Padmini et al, 2020). Hydrophobic interactions seem to be the dominating power for binding, whereas hydrogen bonding and electrostatic interactions likely to influence the precision of the complexation (Nag et al, 2021).…”
Section: Phytochemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structure of chemical compounds identi ed using GC-MS analysis were obtained from the Pubchem database and the three-dimensional protein structure of EGFR protein involved in lung cancer pathogenesis was downloaded from RCSCB protein data bank (PDB) [42]. The Graphical User Interface program "AutoDock Tools" was used to prepare, run, and analyze the docking simulations.…”
Section: In-silico Molecular Docking Of C Subradiata Compoundsmentioning
confidence: 99%
“…A. cepa and A. sativum are potential antimicrobial agents and a recent study reports that Silver nanoparticles synthesized from these species have shown to exert antimicrobial activity against vaginal pathogens Streptococcus pneumoniae and Pseudomonas aeruginosa ( Bouqellah et al, 2018 ). Novel bioactive metabolites from A. sativum have been recently identified as potent anti-cancer drug targets ( Padmini et al, 2020 ). Numerous other vegetables under the Allium genus have significant medicinal values but still remain unrecognized and underutilized.…”
Section: Introductionmentioning
confidence: 99%